Green Consumer Behavior in the Perspective of Green Marketing and Theory of Planned Behavior - Manongko, Allen A. Ch; Tamboto, Henry J. D; Watung, Sjeddie R. (Technium Social Sciences Journal, 2020)
The purpose of this research is to analyze the effects of green marketing and the theory of planned behavior on green consumer behavior. The research design used a quantitative approach through the survey method. The population analyzed in this research are consumers that buy green products and are willing to conduct interviews about green products in modern markets in several districts/cities in the province of North Sulawesi. The research sample analyzed consisted of 381 respondents. A purposive sampling technique employing multiple regression was used, with the help of the application programs SPSS and Ms Excel. The variables in this research are green marketing, the theory of planned behavior, and green consumer behavior. The research findings are: 1) Equation 1 is formed Y = 6.908 + 0.390X1 + e1, meaning that green marketing has both a positive relationship with, and a significant effect on, green consumer behavior; 2) Equation 2 formed Y = 15.437 + 0.677X2 + e2, meaning that the theory of planned behavior had a positive relationship with, and a significant effect on green consumer behavior; 3) Equation 3 formed Y = 7.031 + 0.292X1 + 0.255X2, meaning that green marketing and theory of planned behavior had a positive relationship with, and a significant effect on green consumer behavior. With the contribution of green marketing and the theory of planned behavior, 44% of consumers practice green consumer behavior.